1995
DOI: 10.1289/ehp.95103s923
|View full text |Cite
|
Sign up to set email alerts
|

Immunotoxicity of heavy metals in relation to Great Lakes.

Abstract: Heavy metals including mercury, lead, and cadmium are present throughout the ecosystem and are detectable in small amounts in the Great Lakes water and fish. The main route of exposure of humans to these metals is via the ingestion of contaminated food, especially fish. Extensive experimental investigations indicated that heavy metals alter a number of parameters of the host's immune system and lead to increased susceptibility to infections, autoimmune diseases, and allergic manifestations. The existing limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(27 citation statements)
references
References 110 publications
(147 reference statements)
0
27
0
Order By: Relevance
“…Reviews recently have been published on immunotoxicity and the possible impacts of heavy metals (265), pesticides (266), and PCBs (267) in relation to human health and the Great Lakes.…”
Section: S=c\r-mentioning
confidence: 99%
“…Reviews recently have been published on immunotoxicity and the possible impacts of heavy metals (265), pesticides (266), and PCBs (267) in relation to human health and the Great Lakes.…”
Section: S=c\r-mentioning
confidence: 99%
“…e changes in GST enzyme activity may be reduced in Pb-GSH conjugates and excretion, leading to accumulation of lead in blood. In turn, previous studies also reported that lead could in�uence on suppression of T-helper type 1 cells and enhancement of T helper type 2 ( 2) cells [27,28]. In addition, these 2 cells are signi�cantly related to IL-6 production which played a role in the upregulation of both CRP and �brinogen [29,30].…”
Section: Discussionmentioning
confidence: 88%
“…Exposure to heavy metals in the environment has been related to immunotoxic effects and has been targeted for direct reduction in consumption (e.g. consuming less foods with trace amounts of metals) (134). Heavy metals present in PM appear to be the main culprits impacting mental health via the respiratory system, cardiovascular system and immune system (69,74,86).…”
Section: Discussionmentioning
confidence: 99%